Gastrointestinal parasites of yaks from Katao Valley in North Sikkim, India - PAL, PAPRI; CHATLOD, L R; AVASTHE, R K (The Indian Journal of Animal Sciences, 2014)
Faecal samples (377) of yaks belonging to different age groups and of either sex were collected from November 2010 to October 2011 and examined for the presence of helminthic infections through coproscopy. The occurrence of gastrointestinal parasitic infection was recorded at 15.38% in both the organized and traditionally managed farms of yaks. The status of infection was either single (4.24%) or mixed (11.14.%) with a faecal egg count range of 100–400 eggs / gram of faeces in positive animals. Haemonchus spp. infection was predominant (7.43%) followed by Dicrocoelium spp. (2.39%), Nematodirus spp. (2.12%), Cooperia spp. (1.59%), Ascaroid spp (0.79%), Strongyloides spp (0.53%) and Moniezia spp. (0.53%). The rate of infestation was higher in calves and parasites mostly recorded were Haemonchus spp., Ascaroid spp. and Eimeria spp. The females were found more (16.55%) susceptible to gastrointestinal parasitic infections than the males (11.11%).